In Vitro Anti-AChE, Anti-BuChE, and Antioxidant Activity of 12 Extracts of Eleutherococcus Species - Załuski, Daniel (Oxid Med Cell Longev, 2016)
Neurodegenerative diseases are one of the most occurring diseases in developed and developing countries. The aim of this work focused on the screening of the natural inhibitors of AChE and BuChE and antioxidants in Eleutherococcus species. We found that the ethanol extracts of E. setchuenensis and E. sessiliflorus showed the strongest inhibition towards AChE (IC(50): 0.3 and 0.3 mg/mL, resp.). Among chloroform extracts, the most active appeared to be E. gracilistylus (IC(50): 0.37 mg/mL). In turn, the ethanol extract of E. henryi inhibited the strongest BuChE with IC(50) value of 0.13 mg/mL. Among chloroform extracts, E. gracilistylus, E. setchuenensis, and E. sessiliflorus appeared to be the strongest with IC(50) values of 0.12, 0.18, and 0.19 mg/mL. HPTLC screening confirmed the presence of inhibitors in extracts. All extracts exhibited anti-DPPH(⁎) activity and single antioxidants have been identified. To the best of our knowledge, no information was available on this activity of compounds in Eleutherococcus. These studies provide a biochemical basis for the regulation of AChE and BuChE and encourage us to continue isolation of active compounds.